1988
DOI: 10.1227/00006123-198807000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Intervertebral Disc Herniations: Diagnostic Value of Magnetic Resonance Imaging

Abstract: Thoracic disc herniation is relatively rare and frequently poses a challenge in clinical diagnosis. These protrusions have been categorized into two major anatomical types and three main clinical syndromes. A number of characteristic radiographic features have been reported. Recently, magnetic resonance imaging (MRI) has gained popularity as a neurodiagnostic imaging tool. A series of nine cases of thoracic intervertebral disc herniation is reported. The clinical aspects of the cases are discussed, and the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
8

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 0 publications
3
24
0
8
Order By: Relevance
“…Distribution according to gender showed a marked female predominance in the present series consistent with the literature [4,6,7,9,14,17,19,28,30], perhaps due to changes in the hormonal status during menopause and its consequences on calcium-phosphorus metabolism. In the present series, all of the lesions were observed in the lower half of the thoracic spine with a peak of frequency between the eighth and twelfth thoracic vertebrae.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Distribution according to gender showed a marked female predominance in the present series consistent with the literature [4,6,7,9,14,17,19,28,30], perhaps due to changes in the hormonal status during menopause and its consequences on calcium-phosphorus metabolism. In the present series, all of the lesions were observed in the lower half of the thoracic spine with a peak of frequency between the eighth and twelfth thoracic vertebrae.…”
Section: Discussionsupporting
confidence: 91%
“…Symptomatic HTHD is more frequent during the fourth and fifth decade of life [4,6,7,14,17,22,26,30], in the framework of a spinal degenerative process. Distribution according to gender showed a marked female predominance in the present series consistent with the literature [4,6,7,9,14,17,19,28,30], perhaps due to changes in the hormonal status during menopause and its consequences on calcium-phosphorus metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of ten surgical series (238 patients), 5,6,12,15,23,26,27,39,40,43 we found that the indications for operation were myelopathy in 70% of cases, intractable radiculopathy in 24% of cases, and back pain in 6% of cases. These data are similar to those demonstrated in the present series in which 70% of patients underwent surgery for myelopathy and 30% for radiculopathy.…”
Section: Discussionmentioning
confidence: 98%
“…Because the great majority of thoracic disc herniations remained stable or decreased in size and because no clinical symptoms developed over time, it is difficult to recommend prophylactic surgery for patients with asymptomatic disc herniations. 5,45 No predictors currently exist to indicate which patients with incidentally discovered disc herniations will develop symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…When they do occur, they are typically found in older patients and are predominantly found in the lower thoracic spine [11][12][13]. The most common disc level for thoracic disc herniation was found to be the T11-12 level with 26-50% of the total number [14][15][16]. A classic study reviewing the occurrence of 258 thoracic disc herniations found the majority (66%) occurred in the lower third of the thoracic spine (between T9-10 and T12-L1), then middle third (28% between T5-6 and T8-9), followed least by the upper thoracic spine (6% between T1-2 and T4-5) [17].…”
Section: Discussionmentioning
confidence: 99%